2016
DOI: 10.1590/1981-6723.1015
|View full text |Cite
|
Sign up to set email alerts
|

Spouted bed drying efficiency of bovine hydrolyzed collagen

Abstract: SummaryBovine hydrolyzed collagen (BHC) is an important food supplement normally consumed in the form of capsules or powder in order to stimulate the synthesis of collagen, promote health and assist in esthetics. The transformation of liquid foods into powders by drying is a difficult operation due to the complex physical and chemical changes resulting from the use of high temperatures, which may result in low drying efficiency and unwanted physicochemical and nutritional characteristics in the final product. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The obtained results demonstrated that the use of auxiliary devices such as draft tubes, fountain confiners or the use of specific reactor shapes (such as rectangular SBR) considerably increased drying yields. Butzge and collaborators [26] investigated the efficiency of a conical SBR for drying bovine hydrolysed collagen (BHC). Thanks to several tests at different working conditions, they discovered that the maximum powder production could be obtained by working with polypropylene as inert material and atomisation as feed mode.…”
Section: Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results demonstrated that the use of auxiliary devices such as draft tubes, fountain confiners or the use of specific reactor shapes (such as rectangular SBR) considerably increased drying yields. Butzge and collaborators [26] investigated the efficiency of a conical SBR for drying bovine hydrolysed collagen (BHC). Thanks to several tests at different working conditions, they discovered that the maximum powder production could be obtained by working with polypropylene as inert material and atomisation as feed mode.…”
Section: Dryingmentioning
confidence: 99%
“…Thanks to several tests at different working conditions, they discovered that the maximum powder production could be obtained by working with polypropylene as inert material and atomisation as feed mode. A mechanical modified spouted bed reactor (MMSB) fitted with a helical screw was analysed for the drying of alumina and skimmed milk [26]. The tests showed that the helical screw decreased the air velocities needed for the running of the reactor, decreasing the total energy consumption [27].…”
Section: Dryingmentioning
confidence: 99%
“…Table 3 shows other ingredient used. Butzge et al (2016) developed a powdered food compound that uses natural fruit pulp as a source of antioxidant bioactive compounds rather than artificial aroma and taste. The compound was added to hydrolyzed collagen, obtaining a food supplement that can be directly consumed or be applied as intermediate product in food and beverage production.…”
Section: Eye Healthmentioning
confidence: 99%
“…Its biological properties are notorious for protection of articular cartilages under stress conditions; relief of osteoarthritis and osteoporosis symptoms Puigdellivol et al, 2018); stimulation of bone-forming cells; improvement of calcium absorption ; protection and recovery of connective tissue in response to intense strength and cardiovascular training ; and, lastly, reduction of visible signs of skin natural aging , 2015Proksch et al, 2014). Due to its physicochemical and biological properties, HC has been used in the elaboration of functional fruit pulp beverages, hence improving their nutraceutical characteristics Butzge et al, 2014;Rigoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%